Evaluation of cases of concussion and subluxation in the permanent dentition: a retrospective study - Denise Pedrini; Sônia Regina Panzarini; Adelisa Rodolfo Ferreira Tiveron; Valéria Marisel de Abreu; Celso Koogi Sonoda; Wilson Roberto Poi; Daniela Atili Brandini (University of São Paulo, 2018)
Abstract Objectives This study evaluated the evolution of cases of concussion and subluxation through a retrospective study of 20 years. Material and Methods Were examined clinical and radiographic records of 1,309 patients who underwent treatment of dentoalveolar trauma in the discipline of Integrated Clinic of the School of Dentistry of Araçatuba, UNESP, of which we selected 137 whose patients had concussion and subluxation injuries, with average age of 23.3 (SD - 10.96). The variables collected were: gender, age, history of previous and actual trauma, treatments performed, the presence of necrotic pulp, and time elapsed until the same trauma. The concussion and subluxation groups were subjected to statistical analyses using the SPSS 16.0 version software (α=0.05), Chi-square, and t-tests. Results Of the 301 teeth involved, 49 (16.3%) suffered concussion and 252 (83.7%), subluxation, being the upper anterior teeth the most affected (75.1%) for both conditions. Subluxation and concussion traumas were more prevalent in men aged 10 to 20 years, most caused by cycling accidents (36.2%). There was a concomitant presence of crown fracture in 21% of cases of concussion and 34.7% of subluxation. Pulp necrosis was detected in 16.3% (concussion) and 27.1% (subluxation) (p=0.12), and most occurred within 6 months after the trauma (p=0.29). The pulp necrosis shows a positive correlation with motorcycle accidents (p=0.01), direct impact (p≤0.0001), crown fracture with pulp exposure (p≤0.0001), darkening of the crown (p=0.004) and spontaneous pain (p≤0.0001); and negative correlation with indirect impact (p≤0.0001). Conclusions Although concussion and subluxation traumas are considered of minor degrees, they must be monitored, since the possibility of pulp necrosis exists, and its early treatment favors a good prognosis.